Repopulation of pseudorabies-infected swine herds by embryo transfers - James, J.E.; James, D.M.; Martin, P.A.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Embryos were transferred from two pseudorabies infected herds to recipients from a pseudorabies free herd. All 38 donor sows had serum titers for pseudorabies but no recipients or pigs that were farrowed had clinical signs or serum titers for pseudorabies. In total 805 embryos were transferred to 34 recipient sows and gilts of which 22 (65%) farrowed 208 pigs (189 farrowed alive).
Keywords: Swine; Pseudorabies-infected; Embryo transfers; Sows